Effectiveness of programme 'Exam Smart' in UiTM Penang / Teoh Sian Hoon, Ng Set Foong and Sarina Md Jam - Teoh, Sian Hoon; Ng, Set Foong; Md Jam, Sarina (2006)
This study was done in order to seek solutions for designing a quality instruction and feedback activities to assist students in learning mathematics. With the advent of powerful microcomputer, it is envisaged that quality instruction through multimedia harnessing the attributes of computers to facilitate learning. The purpose of this study was in threefold. First, a systematic and quality instruction with advances of technology was created. Second, a systematic of feedback was created for the learner to take responsibility in directing his or her own learning to develop learning ability. Thirdly, the effectiveness of the quality instruction using technology and feedback activities were investigated. The study was a quasi-experimental study. The treatment modes referred to different strategies, namely mastery learning with technology (MLT), mastery learning without technology (ML), instruction with technology (TT) and the control group (C). In this study the dependent variable was the gain scores. The independent variable was the treatment modes with different strategies, namely MLT, ML, TT and C. This study involved the first semester students. Four classes of engineering students were randomly chosen among the seven classes. The samples consisted of 124 students.